Сократить: а) (1+tg^2x)(1-sinx)(1+sinx) = б) 2sinx*cosx-(sinx-cosx)^2=

kravchenkonata14 kravchenkonata14    3   19.05.2019 01:40    3

Ответы
ум5789 ум5789  12.06.2020 06:57

а)(1+tg^2x)*(1-sinx)*(1+sinx)=1

 б)4cosx sinx-1

2sin(2x)-1 

ПОКАЗАТЬ ОТВЕТЫ
SmartJager SmartJager  12.06.2020 06:57
А)1+tg^2x=1/cos^2x
(1-sin x)(1+sin x)=1^2-sin^2x=cos^2x
Получаем
1/cos^2*cos^2x=1

b)2sin x*cos x=sin 2x
(Sin x-cos x)^2=sin^2 x-2*sin x*cos x+cos^2x=sin^2x-sin 2x+cos^2x;
Получаем
Sin 2x-sin^2 x-sin 2x+cos^2x;
Сокращаем
-sin^2x+cos^2x
Дальше не знаю можно сократить или нет, скорее всего нельзя
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Геометрия